Association of Histological and Clinical Chorioamnionitis With Neonatal Sepsis Among Preterm Infants: A Systematic Review, Meta-Analysis, and Meta-Regression - Villamor-Martinez, Eduardo; Lubach, George A.; Rahim, Owais Mohammed; Degraeuwe, Pieter; Zimmermann, Luc J.; Kramer, Boris W.; Villamor, Eduardo (Frontiers in Immunology, 2020)
Chorioamnionitis (CA) is considered a key risk factor for very preterm birth and for developing early onset sepsis (EOS) in preterm infants, but recent data suggest that CA might be protective against late onset sepsis (LOS). We performed a systematic review and meta-analysis of studies exploring the association between CA and sepsis. A comprehensive literature search was performed in PubMed/MEDLINE and EMBASE, from their inception to 1 December 2018. A random-effects model was used to calculate odds ratios (OR) and 95% confidence intervals (CI). Sources of heterogeneity were analyzed by subgroup and meta-regression analyses. The following categories of sepsis were analyzed: EOS, LOS, unspecified onset sepsis (UOS), culture-proven, and clinical sepsis. CA was subdivided into clinical and histological chorioamnionitis. Funisitis was also analyzed. We found 3,768 potentially relevant studies, of which 107 met the inclusion criteria (387,321 infants; 44,414 cases of CA). Meta-analysis showed an association between any CA and any EOS (OR 4.29, CI 3.63 to 5.06), any LOS (OR 1.29, CI 1.11 to 1.54), and any UOS (OR 1.59, CI 1.11 to 1.54). Subgroup analysis showed that CA was associated with culture-proven EOS (OR 4.69, CI 3.91 to 5.56), clinical EOS (OR 3.58, CI 1.90 to 6.76), and culture-proven LOS (OR 1.31, CI 1.12 to 1.53), but not with clinical LOS (OR 1.52, CI 0.78 to 2.96). The presence of funisitis did not increase the risk of either EOS or LOS when compared with CA without funisitis. CA-exposed infants had lower gestational age (-1.11 weeks, CI -1.37 to -0.84) than the infants not exposed to CA. Meta-regression analysis showed that the lower gestational age of the CA group correlated with the association between CA and LOS but not the with association between CA and EOS. In conclusion, our data suggest that the positive association between chorioamnionitis and LOS may be modulated by the effect of chorioamnionitis on gestational age.